Manajemen Strategi Kepala Sekolah dalam Meningkatkan Mutu Pendidikan di SMP Negeri 5 Purworejo - Daimah, Daimah; Wibowo, Adi (Kartika: Jurnal Studi Keislaman, 2024)
Schools have their own strategies as a center for implementing strategic management to compete. It has become a demand that must be carried out to improve and increase the quality of education. This research aims to explore how schools can improve the quality of education through effective management strategies. The method used is descriptive research with a qualitative approach, where data is collected through observation, interviews, and documentation to get a comprehensive picture of the strategies implemented by the school. The research results show that the quality of education is not only determined by schools as educational resource teaching institutions but is also adjusted to the expectations and views of society, which continue to develop. Quality is an important part of institutional strategy and must be approached systematically using a strategic planning process to defend schools from increasingly fierce competition. In conclusion, school quality in education must meet the needs, hopes, and desires of all stakeholders, with the main focus on students through the leadership of the school principal, the quality of the school itself, learning programs, teaching staff, and students. The target of the principal in the current era as a learning leader is to create school policies that are more focused on student-centered learning services.